For whom the Bell Tolls. Մատեան Ողբերգութեան ՂԲ Բանը և Ջոն Դոնի «Ում համար է ղօղանջում զանգը» - Թեո Մաարտըն Վան Լինտ («Նաիրի» հրատ.)
The article briefly presents the life and work of John Donne (1573- 1631), touching upon his transition from baroque love poet to devout priest, and from Catholic born in a recusant family to Dean of St Paul‘s Cathedral in London. It presents two works written in times of grave illness, the poem A Hymn to God my God in my sickness and a chapter from his Devotions Upon Emergent Occasions (1624), and indicates some of the features comparable with Prayer 92 from Grigor Narekac‗i‘s Book of Lamentation, devoted to the simandron. As far as known, this is the first attempt at a translation of these works in Eastern Armenian. Статья кратко представляет жизнь и деятельность Джон Донна (1573-1631), превращение поэта любви, пишущего в стиле барокко, в священника по призванию, и католика, рожденного в семье рекусантов, в декана англиканского Собора Святого Павла в Лондоне. Два произведения, написанные во время серьезных болезней автора: Гимн Богу моему, написанный во время болезни, и глава из Молитвы по возникающим особым поводам (1624) оказывается возможным сопоставить с молитвой 92 из Книги скорбных песнопений Григора Нарекаци, посвященной симандру. В статье предлагается первый опыт перевода названных произведений Джона Донна на восточно-армянский язык.
Keywords: Նարեկացիական ընթերցումներ; Բանասիրություն